PENINGKATAN PRESTASI BELAJAR IPS MATERI PERJUANGAN MEMPROKLAMASIKAN KEMERDEKAAN MELALUI COOPERATIVE SCRIPT - Dirman, Dirman (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This study aims to improve the learning achievement of social studies subjects struggling to proclaim independence through Cooperative Script learning models. This research was conducted in 2 learning cycles which included planning, implementing, observing, and reflecting activities and each cycle consists of 2 meetings. The results of the study prove the initial conditions before using the Cooperative Script learning model with an average value of 66 with a percentage of learning completeness of 36%. After using the Cooperative Script learning model in the first cycle the average value rose to 77 with the percentage of learning completeness 59%. At the end of the second cycle, the average score became 80 with a percentage of learning completeness 82%. Teacher activities experienced an increase from good criteria (2.64) in the first cycle to be a very good criterion of 3.45 in the second cycle. Student activities also increased from good criteria (2.86) in cycle I to good criteria (3.25) in cycle II. Based on the results of these studies it can be concluded that learning using Cooperative Script learning models on social studies subjects struggle to proclaim independence for students of fifth grade of SD Negeri 3 Kedungurang can improve attitudes towards student learning achievement.